Cannabis produces acute hyperphagia in humans and rodents via increased reward valuation for, and motivation to, acquire food - Catherine Hume; Carrie Cuttler; Samantha L. Baglot; Lucia Javorcikova; Ryan J. McLaughlin; Matthew N. Hill (Proceedings of the National Academy of Sciences, 2025)
With approximately 4% of the world’s population using cannabis, there is a need to better understand its physiological effects. Cannabis consumption acutely promotes food intake (“the munchies”) via delta-9-tetrahydrocannabinol-mediated activation of cannabinoid 1 receptors (CB1R); however, these appetitive effects have not been well characterized. We examined effects of cannabis vapor inhalation on energy and macronutrient intake patterns in human participants and then validated these findings in a translational rat model through which we explored behavioral and physiological mechanisms subserving this response. Vaporized cannabis acutely and robustly increased energy intake. In humans, this occurred in the first 30 min of snack and beverage access, irrespective of dose or gender. In rats, these effects were observed in the first 60 min of food access, irrespective of macronutrient content, satiation, or sex, and were a result of cannabis vapor reducing latency to eat and increasing feeding bout number. Also, cannabis vapor did not change the proportion of macronutrients consumed by human participants and abolished preexisting macronutrient-specific food preferences in rats. Our rat data indicate that cannabis vapor may override homeostatic appetite regulation by increasing motivation to eat and reducing food reward devaluation to promote energy intake. Finally, cannabis vapor did not alter circulating appetite-associated hormones, and these feeding effects were mediated by central, but not peripheral, CB1Rs. This study complements and builds upon previous literature to characterize the appetitive effects of vaporized cannabis and uses a translational approach to examine cannabis-driven energy and macronutrient intake patterns in humans and rodents.